Space-indexed aircraft trajectory tracking - Wahid, M. A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Future Air Traffic Management (ATM) demands that flights to be more efficient while maintaining safety and improving flight predictability. Two major research groups Single European Sky (SESAR) and Next Generation Air Transportation system (NEXTGEN) are progressively researching on the concept of 4D trajectory management which aims to improve flight efficiency by integrating time into the 3D trajectory. Therefore the implementation of time-space based flight guidance controller will be investigated in this paper. Firstly, the reference tracking error equations with respect to the spatial variable is defined and later transformed into a reference tracking error with respect to time. Using nonlinear dynamic inversion, the control law is established to make the aircraft accurately follow 3D+T desired trajectories. A simulation is performed to explore the feasibility of the proposed guidance control law and it was found that the proposed guidance control law is able to accurately follow a 3D+T reference trajectory at the same time follow the overfly time constraint.